Tabu Search Algorithm Based Digital Predistortion of Radio over Fiber (RoF) Link - Manjit Singh, Amandeep Singh Sappal (International Journal of Advanced Science and Technology, 2020)
Due to their unique advantages over conventional optical fiber communication systems, Radio over Fiber (RoF) is gaining popularity. But these systems also suffer from nonlinear effects. Due to this nonlinearity intermodulation distortion prodeucts are produces at the output of the system, which results in the generation of in-band and out-band distortions. This degrades the performance of the RoF link. Digital predistortion can be be used as a linearization techniques for mitigating this nonlinearity. In this paper Tabu search algorithm has been used for parameter estimation and updating of digital predistorter. Simulation results have been presented.